Attitude of Residents of an Arctic Single-Industry Town to Tourism Development (Based on Survey in the Murmansk Oblast) - Ekaterina N. Sharova; Galina V. Zhigunova (Арктика и Север)
The article raises the question of the tourism development possibilities in the conditions of Arctic single-industry towns from the viewpoint of local residents. On the one hand, the tourism sector is a very dynamic and flexible system of various activities, which has a powerful multiplicative effect on the well-being and quality of life of specific territories. On the other hand, single-industry towns as a special type of settlement are generally characterized by a number of features that limit the development of tourism: lack of social infrastructure, dependence on the position of the city-forming enterprise, and low involvement of the local population in the service sector, which has a special local identity. In the conditions of the Arctic territories, additional restrictions arise due to natural and climatic factors and negative demographic trends. At the same time, the so-called “human factor” is of particular importance, reflecting the willingness of local residents to participate in the tourism industry. In order to identify attitudes towards tourism, including ideas about the problems and prospects of its development in the Arctic single-industry towns of Russia, the authors conducted a sociological survey among residents of the Pechenga municipal district in the Murmansk Oblast (n = 456 people) in 2021. The results of the survey revealed the attitude to living in this territory, perceptions of the prospects and barriers to tourism development, readiness to integrate into the tourism industry. Despite the general positive assessment of the tourism development prospects in single-industry towns and interest in the tourism as a whole, the population demonstrates a rather inert life strategy, including low readiness to receive tourism education.